Effect of rainfall variability on cropping windows of Patuakhali and Rangpur Regions - Ahmed, Sharif; Islam, Touhidul; Haque, Abdul; Bhandari, Humnath (International Rice Research Institute, 2024)
Rainfall is a crucial climate variable upon which agriculture relies. Uncertainty in rainfall typically impacts food production. Fluctuations in rainfall quantity and distribution impact agricultural output in rainfed areas, hence directly affecting the nation's economy. Understanding the precipitation pattern is crucial for effective crop management. Farmers face significant challenges due to their weak socioeconomic status, restricted availability of modern farming techniques, and the lack of opportunities to diversify their crop production. These factors hinder the effective use of the nation's water resources (Mandal et al., 2015). Consequently, the conventional rainfed agricultural farming method remains focused on subsistence farming, and smallholder farmers experience food shortages due to variations in precipitation and extreme climatic conditions like droughts and floods.